Fenomena LGBTQ+: Analisis Fitrah Seksualitas Manusia - Suraiya Suraiya (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
LGBTQ+ is a sexual deviance that is rampant in society these days. Some people consider that this sexual disorder is caused by hereditary or genetic factors, but studies have proven that this phenomenon is caused by mis-parenting and environmental factors. In the context of Islamic Education, this sexual perversion is caused by the injury of sexual fitrah. In addition, this disorder is also caused by social factors, culture or bad lifestyle. Islam has taught how to grow the fitrah of sexuality through several stages; starting from the age of 0-2 years, 2-7 years, 7-10 years, 10-14 years to the aqil period of baliqh. The presence of a masculine father figure and a feminine mother who accompanies and educates children according to gender from the time they are born to aqil baligh is the key to the child growing according to the fitrah based on his sexuality. If this phase of caring for sexuality is missed, then the seeds of perversion will grow and strengthen. The efforts to cultivate the fitrah of child sexuality must also be combined with instilling the fitrah of faith since both are the keys, so that the child grows completely according to the will of his God when he is presented to this world. Another very important effort is to pay attention to the child's social environment because association might affect our children’s way of thinking and lifestyle.